A Replication Scheme for Multiple Fragmentations with Overlapping Fragments. (6th August 2016) - Wiese, Lena; Waage, Tim; Bollwein, Ferdinand
Abstract: In this article, we introduce a replication procedure in a distributed database system that supports several fragmentations of the same data table. One application that requires multiple fragmentations is flexible (similarity-based) query answering. The major feature of our replication procedure is that replication and recovery respect the overlaps of fragments stemming from different fragmentations. In this paper we extend the data replication problem by not only considering hard constraints to ensure a fixed replication factor but also adding soft constraints that express desired data locality of fragments. We furthermore analyze the case that there are more fragmentations (leading to the situation that some replication conditions are optional); and we study the influences of data updates (insertions and deletions) on the data distribution.